The Leaching of Natural Dyes from Avocado (Persea Americana Mill) Seeds Using the Ultrasonic-Assisted Extraction Method and Its Application to Cellulose Fibers - Utami, Herti; Agustin, Veni Tri; Novirianti, Luthfiah; Darni, Yuli; Lesmana, Donny; Takagi, Ryosuke (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2021)
The textile industry uses synthetic dyes because they are cheaper and easier to obtain. Moreover, the color availability is guaranteed and more varied. However, these synthetic dyes have a negative impact on health and the environment. The natural dye from avocado (Persea Americana Mill) seeds can become an alternative for synthetic dyes. Polyphenol compounds, such as tannins and flavonoids, are natural color sources found in avocado seeds. The extraction of natural dyes from avocado seeds is carried out by using a non-conventional method, namely ultrasonic-assisted extraction which has great efficiency and short operating time. In this study, researchers examined the parameters that affect the yield of dye extraction from avocado seeds, namely solvent concentration and extraction time. In addition, researchers also conducted qualitative analysis on the pigment content in the yield of extraction using UV-Visible Spectrophotometry and GC-MS tests. The results indicated that the highest yield obtained from avocado seeds was 16.6742% with 90 minutes extraction time using 70% ethanol solvent. Furthermore, if the dye is applied to cellulose fibers, such as the cotton cloth, the color will change depending on the fixator added. Based on the result of the UV-Visible Spectrophotometry test, the avocado seeds contain flavonoids. Meanwhile, from the result of the GC-MS test, the compound with the largest percentage detected in avocado seeds is the 13-Tetradecynoic acid, methyl ester (C15H26O2). The compound contains a chromophore, such as a carbonyl group (C = O) which is a common feature of flavonoids.